Pemberian Visioterapi Dada Terhadap Efektifitas Bersihan Jalan Nafas pada An. N Dengan Pneumonia di Wilayah Kerja Puskesmas Karang Taliwang Kota Mataram - Muhammad Moza'i (Gema Cendekia Institute, 2025)
Pneumonia is an acute infection affecting the lung tissue, which may be caused by various microorganisms such as viruses, fungi, or bacteria. One of the most common nursing problems observed in children with pneumonia is ineffective airway clearance, resulting from the inflammatory process within the lungs. Based on the assessment conducted on November 16, 2023, it was found that patient N, a 7-year-old child, was medically diagnosed with pneumonia and presented with complaints of shortness of breath, productive cough, and runny nose with secretions. The respiratory rate was 30 breaths per minute, and additional breath sounds (rhonchi) were heard. According to the Indonesian Nursing Diagnosis Standards (SDKI), the nursing diagnosis established was ineffective airway clearance related to retained secretions. The nursing interventions were formulated according to the Indonesian Nursing Intervention Standards (SIKI), specifically airway management, by applying evidence-based nursing (EBN) through the administration of chest physiotherapy. The goal of the intervention was to assist in the removal of airway secretions. The nursing care was implemented over three visits, with chest physiotherapy administered twice daily—at 09:30 a.m. and 04:30 p.m. Each session lasted for 1–2 minutes and was repeated over a duration of 10–15 minutes. Following the implementation of nursing interventions, the patient's nursing problem was resolved. The expected outcomes were achieved, as evidenced by a patent airway (no additional breath sounds), decreased secretion accumulation, and effective secretion expectoration during coughing. After three days of chest physiotherapy, approximately 40 cc of secretions were expelled, the respiratory rate returned to normal (22 breaths per minute), and the effectiveness of coughing improved. Conclusion: Chest physiotherapy was found to have a positive effect on the effectiveness of airway clearance in children experiencing ineffective airway clearance associated with pneumonia.